2002
DOI: 10.1002/ajim.10034
|View full text |Cite
|
Sign up to set email alerts
|

Results of an intervention to improve lead safety among painting contractors and their employees*

Abstract: Motivated contractors and their employees can make moderate improvements in lead-safe practices if provided with extensive training and technical assistance. Changes that are costly, unfamiliar, or perceived as a threat to work quality are more difficult to implement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The process, location, and environment are typically in a state of constant change as opposed to other sectors such as manufacturing where these factors are more static, and more easily controlled through design and engineering. Nonetheless, successful intervention strategies to lower lead exposures among construction have been performed previously [Vork et al, 2001;Materna et al, 2002]. The number of samples for lead and the number of OSHA visits where lead was sampled decreased throughout the 1990s and leveled off in the 2000s to the lowest levels since quantitative sampling results were entered in IMIS.…”
Section: Discussionmentioning
confidence: 99%
“…The process, location, and environment are typically in a state of constant change as opposed to other sectors such as manufacturing where these factors are more static, and more easily controlled through design and engineering. Nonetheless, successful intervention strategies to lower lead exposures among construction have been performed previously [Vork et al, 2001;Materna et al, 2002]. The number of samples for lead and the number of OSHA visits where lead was sampled decreased throughout the 1990s and leveled off in the 2000s to the lowest levels since quantitative sampling results were entered in IMIS.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis is laid on improvement in interpersonal relationship and stipulate appropriate support to improve occupational health of employees. Materna et al (2002) did a study among painting contractors and their workers about lead safety in San Francisco, USA. They found that positive variations can be reached through widespread training and succor in technical know-how.…”
Section: Introductionmentioning
confidence: 99%
“…Various control measures to decrease BLL of workers should be implemented. Work instruction, training and health education 25,26) , as a fundamental tool can bring about improvements in lead-safe practice and prevention of occupational disease; and such training should be repeated at least annually for each boat-repair worker, as is already implemented among lead-exposed Thai workers in the formal employment sector. In addition, boat-repair workers should be made aware of the risk to their family and encouraged to shower and wash after the work shift to reduce the magnitude of take-home lead.…”
Section: Implications Regarding Reduction Of Lead Contaminationmentioning
confidence: 99%